FORMATION OF VALUE ORIENTATIONS JUNIOR SCHOOLCHILDREN IN THE PROCESS OF STUDYING UKRAINIAN SONG FOLKLORE - Lyubar, R.O. (Pedagogy of Higher and Secondary Education, 2010)
The meaning of spiritual values and values of orientations in system of national edu cation of growing up generation is opened. Is considered Ukrainian national songs creativity as one of means of formation of spiritual values of the younger schoolboys.